Humoral autoimmune response heterogeneity in the spectrum of primary biliary cirrhosis - Dellavance, Alessandra [UNIFESP] (2013)
To compare autoantibody features in patients with primary biliary cirrhosis (PBC) and individuals presenting antimitochondria antibodies (AMAs) but no clinical or biochemical evidence of disease.A total of 212 AMA-positive serum samples were classified into four groups: PBC (definite PBC, n = 93); PBC/autoimmune disease (AID; PBC plus other AID, n = 37); biochemically normal (BN) individuals (n = 61); and BN/AID (BN plus other AID, n = 21). Samples were tested by indirect immunofluorescence (IIF) on rat kidney (IIF-AMA) and ELISA [antibodies to pyruvate dehydrogenase E2-complex (PDC-E2), gp-210, Sp-100, and CENP-A/B]. AMA isotype was determined by IIF-AMA. Affinity of anti-PDC-E2 IgG was determined by 8 M urea-modified ELISA.High-titer IIF-AMA was more frequent in PBC and PBC/AID (57 and 70 %) than in BN and BN/AID samples (23 and 19 %) (p < 0.001). Triple isotype IIF-AMA (IgA/IgM/IgG) was more frequent in PBC and PBC/AID samples (35 and 43 %) than in BN sample (18 %; p = 0.008; p = 0.013, respectively). Anti-PDC-E2 levels were higher in PBC (mean 3.82; 95 % CI 3.36-4.29) and PBC/AID samples (3.89; 3.15-4.63) than in BN (2.43; 1.92-2.94) and BN/AID samples (2.52; 1.54-3.50) (p < 0.001). Anti-PDC-E2 avidity was higher in PBC (mean 64.5 %; 95 % CI 57.5-71.5 %) and PBC/AID samples (66.1 %; 54.4-77.8 %) than in BN samples (39.2 %; 30.9-37.5 %) (p < 0.001). PBC and PBC/AID recognized more cell domains (mitochondria, nuclear envelope, PML/sp-100 bodies, centromere) than BN (p = 0.008) and BN/AID samples (p = 0.002). Three variables were independently associated with established PBC: high-avidity anti-PDC-E2 (OR 4.121; 95 % CI 2.118-8.019); high-titer IIF-AMA (OR 4.890; 2.319-10.314); antibodies to three or more antigenic cell domains (OR 9.414; 1.924-46.060).The autoantibody profile was quantitatively and qualitatively more robust in definite PBC as compared with AMA-positive biochemically normal individuals.